Root induction on siam orange (Citrus nobilis Lour.) originated from Kampar using in vitro shoot in MS media enriched with IBA and NAA - Rasyidah Ulfa; Mayta Novaliza Isda (Jurnal Biologi Universitas Andalas, 2020)
Siam orange (Citrus nobilis Lour.) is a prominent agriculture commodity in Riau province. It tastes sweet, with fragrant aroma and thin skin. Its cultivation, however, needs improvement to gain better quality of product. One effort that is using the in vitro culture. The study aimed to determine the best IBA and NAA concentrations to trigger root formation on siam orange transplant and used Completely Randomized Design (CRD). The result showed that the rooting reached 100% on all treatments. The fastest rooting was observed in 2 mg/L IBA treatment (7.67 days after planting). The most root growth was obtained with combination of 0.5 mg/L NAA with 1.5 mg/L IBA (2.67 units). The longest root was obtained through the mixture of 1.5 mg/L NAA with 0.5 mg/L IBA (2.27 cm).